Concept of Switra in Ayurveda- A Review - Das, Srabani (International Research Journal of Ayurveda & Yoga, 2022)
In the treatise of Ayurveda, Switra is presented as a cutaneous pigmentation disorder, clinically characterized by white spots over the skin. In Ayurveda, though Switra is mentioned along with other types of Kustha, the difference between Switra and Kustha is based on the non-secretary and non-infectious nature of Switra. Switra is caused due to vitiation of Tridosa and Dhatussuch as Rasa, Rakta, Mamsa and Medas. Switra can be correlated with Vitiligo. Vitiligo is described in modern medicine as an autoimmune disease which manifests as a white spot on the skin. Vitiligo is the most common pigmentation disorder affecting 1%-2% of the population worldwide. About 80% of Vitiligo risk is attributable to genetic factors, and the rest 20% is attributable to the environment. It is occurring in both children and adults and is considered the most common pigmentation skin disorder in the world. Vitiligo is considered a cosmetic problem, although its effects can be psychologically devastating, often with a considerable burden on daily life.